Intrahepatic cholestasis of pregnancy and associated causes of death: a cohort study with follow-up of 27-46 years - Suvi-Tuulia Hämäläinen; Kaisa Turunen; Kari J. Mattila; Markku Sumanen (BMC, 2018)
Abstract Background The aim of this study was to determine whether intrahepatic cholestasis of pregnancy (ICP) is associated with causes of death during on average 35 years follow-up after the delivery. Methods The study population comprised 571 women with ICP in at least one pregnancy seen at Tampere University Hospital, Finland, between 1969 and 1988. ICP was verified from patient records. The previous and following subjects in the maternity ward diary were taken as controls for each ICP case. In total, there were 1333 controls. All underlying causes of death were obtained from Statistics Finland in March 2017. The deaths occurred during 1971-2015 and the causes of death were classified according to ICD-10. Results Altogether, 39 of the mothers with ICP (6.8%) and 111 of the controls (8.3%) had died by the end of 2015 (p = 0.267). There were more underlying causes of death from gastrointestinal diseases (15%) in the ICP group than in the control group (4%) (p = 0.011). The number of underlying causes of death due to diseases of the circulatory system were lower in the ICP group (13%) than in the control group (26%), although the finding was not statistically significant (p = 0.088). Moreover, neoplasms were the underlying cause of death in 46% of cases among mothers with ICP and in 41% of cases among the controls (p = 0.609). Diseases of the other organ systems were rare in both groups. Conclusion Women with a history of ICP do not have an increased overall mortality. However, deaths from gastrointestinal diseases are overrepresented among women with a history of ICP.